NANO-ENABLED MATERIALS IN FOOD INDUSTRY AND THEIR POTENTIAL HAZARDS TO HUMAN HEALTH AND ENVIRONMENT - S. MORYA; A.DANQUAH-AMOAH; D.K.THOMPKINSON; S.ROUT (International Journal of Pharma and Bio Sciences, 2016)
Nanotechnology is regarded as one of the most transformative technology of 21st century, which has potential to upgrade scientific innovation while tremendously giving advantage to the society. The applications of nanotechnology in food sector are food safety (e.g., detection of pathogens in food), food security (e.g., intelligent, active, and smart packaging systems), food processing (e.g., encapsulation of flavor or odor enhancer; food textural or quality improvement; new gelation or viscofying agents). Nano-enabled materials (NEMs) are manufactured with a dimension of less than 100 nm. The use of these nano-enabled materials (NEMs) in food contact substances is considered to improve functionality of food product. Nano-enabled materials (NEMs) are desirable for food packaging application due to increased surface reactivity and dispersibility. Hence, it is necessary to do research in this area to adequately characterize potential human exposure and risk associated with the migration of nano-particles from food packaging. There is need to pay special attention to nano-ecotoxicology and guidelines and regulatory documents related to the use of nano-enabled materials in agriculture and food industry. In addition to anxiety the health and environmental effects of nano foods intake, user are also solicitous about ethical or moral issues, including labeling and the right to select, betterment of human abilities, and naturalness of food supply. We should continue to be stalwart against the potential hazards and ethical issues that the application of this new transformative technology. Overall this paper gives an overview on the application of nanotechnology in Food industry.